Evidence for the Nuclear Location of the Genes for Chloroplast IF-2 and IF-3 in Euglena - Kraus, Betsy L. (1988)
The chloroplast translational initiation factors IF-2 and IF-3 from Euglena gracilis are present in low levels in dark-grown cells and can be induced by exposure of cells to light. Studies of the antibiotic sensitivity of the light induction of these factors indicates that both are encoded in the nuclear genome.